On 2D massless field wave equations - Ovcharenko, I.E.; Stepanovsky, Yu.P. (Вопросы атомной науки и техники, 2012)
The 2D wave equations of massless fields with arbitrary spin are obtained by application of the Extended Little Lorentz Group. The possibility of the existence of an interaction of charged 2D massless fields of spin one or higher with the external electromagnetic field is investigated.